Membangun Budaya Literasi melalui Media Baca Elektronik di UPT SDN 067775 Medan Johor - Sigalin, Susanthio Theresia; Purba, Arif Marizki; Ritonga, Fajar Utama (Medan Resource Center, 2023)
Field Work Practice (Internship) Activities paired with MBKM (Campus Teaching Collaboration with USU Batch 2) which is carried out for approximately 4 months, with this activity taking place at UPT State Elementary School 067775 Medan Johor, led by Mrs. Darmiati S.Pd as the head of UPT. Campus Teaching is a program that provides an opportunity for students to learn outside the classroom for one semester by becoming teacher partners to innovate in the development of creative and innovative teaching strategies and models in the target educational unit, with a focus on improving the literacy and numeracy skills of students in schools. Literacy and numeracy are general and fundamental competencies. I was entrusted to teach in grades 5 and 6, where their interest in reading is limited. I created creative learning methods by promoting literacy through electronic media. What I did to support students with limited interest in learning was: Emotional engagement, Creating a comfortable and safe learning environment, Encouraging children to learn while playing. In conducting the learning process, I used electronic media (smartphones) to watch YouTube videos, TikTok learning videos, etc., Giving attention to the children, Providing learning motivation. Literacy is broadly defined as linguistic skills such as listening, speaking, reading, and writing, as well as the cognitive abilities that are components of it.